Investigation of outbreaks of salmonella in hospitals. Issue 6396 (24th September 1983) - Palmer, S R; Rowe, B
Abstract : In a two year prospective survey of outbreaks of salmonella infection in hospitals in England and Wales 55 outbreaks were identified. Reports of investigation of these outbreaks were reviewed for evidence of food borne infection and cross infection. Food borne infection probably accounted for only six outbreaks, but these made up 40% of the 15 outbreaks in which there were more than five patients and staff with symptoms. Person to person transmission was the probable mode of spread in most outbreaks. It is recommended that in addition to bacteriological investigations clinical and epidemiological data should be collected to implicate food or other possible common vehicles of infection. Bacteriological screening of patients and staff who do not have symptoms may be unrewarding in the absence of epidemiological data to define groups at risk of infection.